Faktor-Faktor yang Mempengaruhi Kepatuhan Wajib Pajak Orang Pribadi di Jakarta Pusat - Vanessa Kristiani; Maulana Malik Muhammad (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
The purpose of this study is to find out influence knowledge on taxpayers, awareness on taxpayers, service quality on taxpayers, assertiveness tax sanctions to taxpayer, and taxation socialization on individual tax payer compliance in Central Jakarta. This study uses primary data obtained directly through the distribution of questionnaires with a sampling method is purposive sampling. The respondents of this study are individual taxpayers in Central Jakarta with a sample of 124 respondents. The results of this study indicate that the variable knowledge of taxpayers and awareness of taxpayers are effecting on taxpayer compliance, while for the variable quality of tax services, the assertiveness of tax sanctions, and socialization of taxation are not effecting on tax payers compliance.